Land Use Change and its Impact on Vegetation Cover in Tingo María National Park, between the years 2006-2021 - Zuloaga-Obregón, José Luis (2023)
This article is developed with the purpose of analyzing land use changes and their impact on vegetation cover within the Protected Natural Area (PNA) Tingo María National Park (TMNP) and identifying the territorial actors and agents linked to these changes, between the years 2006 and 2021. To achieve this, qualitative methodologies have been applied, including semi-structured interviews and non-participant observation, as well as quantitative methodologies through the processing of satellite images to determine land use change rates. The results show that during the studied years, there are changes in the intervened soil cover and vegetative cover, both located in the Special Use and Buffer Zones of the National Park, which are associated with extensive agricultural practices for subsistence and local markets. Local population, organized with park managers, universities, and local and regional institutions, participate in the management of TMNP. It is concluded that, over the studied period, the coverage changes, unlike other PNAs, have not been significant as in others due to the joint actions of institutional actors and the local population that have halted the emergence of illegal and unauthorized activities that could directly impact the vegetative cover of TMNP. This represents an effective management model for a natural space that provides various ecosystem services.